Effect of the water spray stress on swirling fluidized bed height - Naz, M.Y. (Asian Research Publishing Network, 2015)
This study was designed to investigate the effect of spray stress and pressure drop on the height of a swirling fluidized bed of plastic beads. The motivation for conducting this work was primarily an interest in elaborating the fluidized particles response to the water sprayed from top of the bed. It is revealed that the bed height is greatly influenced by both parameters: the pressure drop and spray stress regardless of the bed weight. The air pressure above the bed abruptly decreased with the spray stress whereas an increasing trend in pressure was depicted just below the bed. The increased pressure difference across the bed suddenly lifted the plastic beads from packed to minimal fluidization, then to slug-wavy followed by swirling and a vigorously bubbling bed with lower layer swirling. Overall the height of the bed exposed to the top spray was higher than that without the spray stress. The height of the settled bed of 200 g beads was calculated as 140 mm, which increased to 200 mm with pressure drop of 150 mmH2O. Â© 2006-2015 Asian Research Publishing Network (ARPN).